An Analysis on Ibn Khaldun's Methodology in Social Change - Halim, Harliana; Yusoff, Kamaruzaman; Basir, Aminuddin; Md. Yusoff, Rosman; Sarawati Johar, Siti; Hisyam Abdul Rahim, Mohd; Suraya Aziz, Hani; Shakor Borham, Abdul (International Journal of Engineering and Technology, 2018)
In the realms of historical sociology, Ibn Khaldun is a name that strikes absolute familiarity among experts. However, the discussions expressed in historical sociology debates do not specify how Ibn Khaldun's ideas and thoughts were actually focusing on social changes that occur in a society. Hence, the discussion of this article will analyse the approaches and methodologies applied by Ibn Khaldun in analysing the social changes that took place during his lifetime and prior to it, as recorded in Muqaddimah Ibn Khaldun. This paper uses a historical descriptive qualitative research approach. Facts were analysed using a text analysis approach in understanding Ibn Khaldun's methodology on social change and Muqaddimah Ibn Khaldun, assisted by induction and deduction approaches. As a result, the researcher found that Ibn Khaldun applied a diversity of approaches in discussing social changes which encapsulate humanitarian, historical philosophy, inquiry, logic and metaphysical, critical and critique, realistic, inductive and deductive, comparative, observational and participatory approaches in studying social changes issues. In addition, he also applied a combination of critical approaches and contextual knowledge, as well as thematic and descriptive approaches in writing. This proves how significant the social changes issues were to Ibn Khaldun, thus they needed to be monitored and managed wisely.Â Â
Keywords: Ibn KhalduÌ„n; Methodology; Social Change